2015
DOI: 10.1177/1557988315576775
|View full text |Cite
|
Sign up to set email alerts
|

Men Who Have Sex With Men in Peru: Acceptability of Medication-Assisted Therapy for Treating Alcohol Use Disorders

Abstract: In Peru, the HIV epidemic is concentrated in men who have sex with men (MSM) and transgender women (TGW). Multiple studies correlate alcohol use disorders (AUDs) with risky sexual behaviors among Peruvian MSM. Qualitative research was used to inform a clinical trial on the acceptability of medication-assisted therapies (MAT) to assist management of AUDs and improve antiretroviral therapy (ART) adherence among MSM/TGW in Peru. Three focus groups involving HIV-infected or HIV-uninfected MSM/TGW (n=26) with AUDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…As previously reported (Brown et al, 2015), participants were mostly young (mean=28.3 years; range=20–40 years). Socioeconomic information was not recorded.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As previously reported (Brown et al, 2015), participants were mostly young (mean=28.3 years; range=20–40 years). Socioeconomic information was not recorded.…”
Section: Resultssupporting
confidence: 65%
“…The first four themes are discussed herein; the latter three were published recently (Brown et al, 2015). …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A systematic review and meta-analysis, however, showed no differences between most pharmacological agents in their ability to reduce relapse to any alcohol use but did find a reduction in days of heavy drinking for most approved (i.e., naltrexone and acamprosate) and some off-label medications [102]. The acceptability of pharmacological treatments for AUDs, however, will be crucial for their uptake [103]. The extent to which alcohol reduction, rather than complete elimination of use, will translate to improvements in each step of the HIV treatment cascade remains likely but unknown and needs empiric support from prospective controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that apply across high-risk populations should be pursued. However differing perceptions of alcohol abuse and cultural acceptability of social alcohol use in excess (Brown et al, 2015), may be hindering participation in alcohol abuse treatment programs. Therefore it is of critical importance that community engagement informs how interventions addressing unsafe alcohol use can be better accessed across high-risk populations.…”
Section: Discussionmentioning
confidence: 99%